Enhancing Wayfinding in Healthcare Facilities: A Comparative Study on the Impact of Universal Design Principles - Usman, Abdullahi Haruna; Sagir, Abdullahi; Zakari, Abdullahi Tijjani (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
The focus of this study is on the influence of universal design principles on wayfinding effectiveness in healthcare facilities with a focus on improving navigation success and reducing stress and anxiety among patients, visitors and staff. Three hospitals with varying levels of universal design principles were selected as case studies. A comprehensive checklist rooted on the principles of universal design was used to evaluate the presence and effectiveness of these principles in each hospital, assessing aspects such as signage, layout, and digital wayfinding tools. Additionally, in-depth interviews were conducted with hospital users, including patients, visitors, and staff, to gather information about their navigation experiences, challenges faced, and suggestions for improvement. The results showed that hospitals with more universal design principles had more effective wayfinding performance, with users reporting higher navigation success rates, fewer challenges, and greater overall satisfaction. The findings suggest that incorporating universal design principles into healthcare environments can improve wayfinding performance, reduce stress and anxiety, and enhance the overall patient experience. This research underscores the need to prioritize the principles of universal design in healthcare design and management, and provides recommendations for implementing these principles in practice.